Development and Initial Evaluation of a Flying Robot-Based Trainer Kit for Robotics Learning - Nur Alamsyah; Muhammad Yaumi; M. Shabir U; Muh. Rapi (Information Technology Education Journal, 2026)
Purpose – Robotics learning in higher education requires the integration of conceptual understanding and practical skills, yet the availability of learning media that effectively bridges theory and practice remains limited. This study aimed to develop a flying robot–based Trainer Kit learning media for robotics courses and to examine its feasibility through expert validation, practicality evaluation, and a limited trial of student learning outcomes. Design – The study employed a research and development (R&D) approach using the Four-D model, limited to the Define, Design, and Develop stages. A limited trial was conducted using a one-group pretest–posttest design involving 12 students enrolled in a Robotics course. Findings – The validation results showed an average score of 4.20 from media experts and 4.33 from material experts (very valid category). The practicality questionnaire results indicated high usability, with average scores of 4.53 from students and 4.38 from lecturers (very practical category). Student learning outcomes improved from a mean pretest score of 56.58 to a posttest score of 89.25, with an average N-Gain of 0.75 (high category). A paired-samples t-test indicated a statistically significant improvement (p < 0.001) with a very large practical effect (Cohen’s d ≈ 9.23). Research implications –  These findings indicate that the developed learning media is valid and practical and showed improved learning outcomes in a limited trial (N=12). However, the results should be interpreted as preliminary evidence due to the one-group design and small sample size. Originality – This study develops and evaluates a flying robot–based Trainer Kit as an innovative learning media to bridge theory and practice in robotics education.